2002
DOI: 10.1111/1467-9310.00270
|View full text |Cite
|
Sign up to set email alerts
|

Suggestion systems: transferring employee creativity into practicable ideas

Abstract: Nowadays many companies are aware of the importance of employee creativity. Suggestion systems are among the instruments for channelling creativity. However, companies vary strongly in the success with which they use suggestion systems. This article aims to clarify the organisational conditions for the successful use of suggestion systems. The CreativityTransformation Model encompasses the main factors that influence the functioning of suggestion systems. The model is tested within specific divisions of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
137
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(149 citation statements)
references
References 21 publications
1
137
0
9
Order By: Relevance
“…However, they still struggle to improve the innovative results of these systems as they mostly produce incrementally rather than radically new propositions (Fairbank and Williams 2001;Van Dijk and van den Ende 2002;Amin and Roberts 2008). To overcome this issue, organizations increasingly engage in knowledge exchange through communityoriented efforts among employees.…”
Section: Introductionmentioning
confidence: 99%
“…However, they still struggle to improve the innovative results of these systems as they mostly produce incrementally rather than radically new propositions (Fairbank and Williams 2001;Van Dijk and van den Ende 2002;Amin and Roberts 2008). To overcome this issue, organizations increasingly engage in knowledge exchange through communityoriented efforts among employees.…”
Section: Introductionmentioning
confidence: 99%
“…Also Deichmann (2012), Dickinson (1932), Fairbank and Williams (2001), Reuter (1997), Van Dijk and Van den Ende (2002) in the studies admitted that aim of IM is to stimulate, support and channel employee ideas. Authors of the research would like to admit that IM is not restricted to some limited idea sources or idea managers (idea generators, evaluators).…”
Section: Discussion On Immentioning
confidence: 99%
“…"Word cloud" see in Figure 1. Passive IMS according to Brem, Voigt (2007) and Van Dijk, Van den Ende (2002) could be called suggestion systems which prefers extraction of ideas, idea identification, idea flow-up, but Westerski, Dalamagas, Iglesias (2013) calls it suggestion boxes, but also revealed that these are less sophisticated systems than active. Gamlin, Yourd and Patric (2007) named passive IMS as classical IMS and manifested that in these IMS employees are encouraged to submit any idea that comes to mind, but unfocused also Brem and Voigt (2007) determined that the aim of this system is to harness employees' creativity.…”
Section: Discussion On Immentioning
confidence: 99%
“…Van Dijk et Van Den Ende (2002) figurent parmi les rares chercheurs à avoir étudié un grand nombre de ces programmes. Ils ont ainsi pu en identifier qui génèrent des résultats remarquables comparativement à la moyenne et ont, dans une deuxième étape, réalisé une étude plus approfondie de ces programmes exceptionnels.…”
Section: éTudier Davantage Le Management Des Idées Dans La Pmeunclassified
“…Comme le suggèrent Carrier et Gélinas (2011), le modèle de Van Dijk et Van Den Ende (2002) de transformation des idées en réalisations concrètes pourrait servir de base aux réflexions de gestionnaires songeant à instaurer un programme de management des idées. Ce modèle comporte trois phases : l'extraction des idées, l'atterrissage ou prise en compte de celles-ci et les suites menant à leur concrétisation.…”
Section: éTudier Davantage Le Management Des Idées Dans La Pmeunclassified